Analysis of Protection and Recovery Efforts Against Victims of Domestic Violence Especially Children and Women - Saputra, Reza (Journal of Social Research, 2023)
Domestic violence is a distressing criminal offense that can result in severe legal repercussions, including imprisonment, as well as profound and lasting effects on its victims. This pervasive issue often involves one family member inflicting harm on another within the confines of their own home. Discussing domestic violence is no longer a societal taboo, as awareness has grown about the importance of addressing and preventing such cases. The motives behind domestic violence are complex, stemming from issues like relationship disharmony, financial strain, poor communication, and more. These underlying factors can trigger a range of abusive behaviors, leading to physical, emotional, and psychological harm for the victims. These abuses can manifest directly or indirectly, through threats, manipulation, or physical violence. The consequences of domestic violence are not limited to the short term; they can have enduring effects on the victims' lives. Physically, victims can sustain injuries that may require medical attention, while the emotional and psychological scars can linger, affecting self-esteem, mental health, and overall well-being. It is crucial to address this issue through legal means, support, and education to break the cycle of domestic violence and protect its victims.